The private and public insurance value of conservative biodiversity management - Stefan Baumgärtner; Martin Quaas (UFZ-Umweltforschungszentrum Leipzig-Halle, 2005)
The ecological literature suggests that biodiversity reduces the variance of ecosystem services. Thus, conservative biodiversity management has an insurance value to risk-averse users of ecosystem services. We analyze a conceptual ecological-economic model in which such management measures generate a private benefit and, via ecosystem processes at higher hierarchical levels, a positive externality on other ecosystem users. We find that ecosystem management and environmental policy depend on the extent of uncertainty and risk-aversion as follows: (i) Individual effort to improve ecosystem quality unambiguously increases. The free-rider problem may decrease or increase, depending on the characteristics of the ecosystem and its management; in particular, (ii) the extent of optimal regulation may decrease or increase, depending on the relative size of private and external effects of management effort on biodiversity; and (iii) the welfare loss due to free-riding may decrease or increase, depending on how biodiversity influences ecosystem service provision; it increases, unless higher biodiversity greatly decreases the variance of ecosystem services.
Keywords: 330; biodiversity; ecosystem services; ecosystem management; free-riding; insurance; public good; risk-aversion; uncertainty; Biodiversität; Umweltpolitik; Trittbrettfahrerverhalten; Entscheidung bei Unsicherheit; Risikoaversion; Versicherungsprämie; Externer Effekt; Theorie